The function and design of seclusion rooms in clinical settings. (1st September 2017) - Kaar, Stephen; Walker, Helen; Sethi, Faisil; McIvor, Ronan
Aim: Following a review of the evidence base, this paper aims to provide recommendations for the design of safe and therapeutic seclusion rooms across clinical settings from general adult mental health to forensic mental health.Method: A review of the existing literature on seclusion design was performed using Embase, Ovid Medline, PsychINFO, HMC Health Management Consortium and generic search engines such as Google and Google Scholar.Results: The evidence base for the optimum design of seclusion rooms is poor, and is mostly qualitative, descriptive or based on expert opinion. Themes were extracted from the available literature, including existing government and legal guidelines, environmental design theory and clinical expertise.Clinical implications: This review establishes a number of recommendations for the optimum design of seclusion rooms and proposes a standardised model of seclusion rooms across psychiatric settings in the interest of improving patient care across clinical settings.